Disrupting Dimerization Translocates Soluble Epoxide Hydrolase to Peroxisomes - Nelson, Jonathan W. (PLoS One, 2016)
The epoxyeicosatrienoic acid (EET) neutralizing enzyme soluble epoxide hydrolase (sEH) is a neuronal enzyme, which has been localized in both the cytosol and peroxisomes. The molecular basis for its dual localization remains unclear as sEH contains a functional peroxisomal targeting sequence (PTS). Recently, a missense polymorphism was identified in human sEH (R287Q) that enhances its peroxisomal localization. This same polymorphism has also been shown to generate weaker sEH homo-dimers. Taken together, these observations suggest that dimerization may mask the sEH PTS and prevent peroxisome translocation. In the current study, we test the hypothesis that dimerization is a key regulator of sEH subcellular localization. Specifically, we altered the dimerization state of sEH by introducing substitutions in amino acids responsible for the dimer-stabilizing salt-bridge. Green Fluorescent Protein (GFP) fusions of each of mutants were co-transfected into mouse primary cultured cortical neurons together with a PTS-linked red fluorescent protein to constitutively label peroxisomes. Labeled neurons were analyzed using confocal microscopy and co-localization of sEH with peroxisomes was quantified using Pearson’s correlation coefficient. We find that dimer-competent sEH constructs preferentially localize to the cytosol, whereas constructs with weakened or disrupted dimerization were preferentially targeted to peroxisomes. We conclude that the sEH dimerization status is a key regulator of its peroxisomal localization.